Trepopnea associated with paroxysmal severe tricuspid regurgitation triggered at left lateral decubitus position - Wolf, David Gregor; Benz, Andreas; Hardt, Stefan; Katus, Hugo; Mereles, Derliz (Echocardiography, 2010)
A 78-year-old male patient was referred cardiovascular risk evaluation before elective resection of a bronchial carcinoma. A myocardial infarction with a subsequent coronary artery bypass revascularization and a mitral prosthetic valve surgery were known. Left lateral decubitus (LLD) was permanently avoided because of significant trepopnea since several years. No signs of heart failure were found in the physical examination. A mitral valve prosthesis presented normal characteristics at examination. Left ventricular dimensions and function were normal. A severe tricuspid regurgitation could be documented during examination in the LLD, with changing characteristics in dorsal decubitus, when it could be graded as moderate. Trepopnea associated with severe paroxysmal tricuspid regurgitation was never described before in the literature. Sympathetic/parasympathetic modulation of papillary muscles of the tricuspid valve can be proposed as a probable cause of this dynamic valvular dysfunction. (Echocardiography 2010;27:E77-E79)